Effect of isomorphic problems with feedback to reduce student misconceptions on simple harmonic motion - Khusaini Khusaini; Ivan Danar Aditya Irawan; Bakhrul Rizky Kurniawan (Universitas PGRI Kanjuruhan Malang, 2025)
This research aims to investigate the effect of isomorphic problems with feedback to reduce student misconceptions about Simple Harmonic Motion. This study is quantitative research with One Group Pretest-Posttest Design. Respondents were given pretest and posttest using a four-tier diagnostic test instrument. A sample of 33 students from Grade XI IPA was selected using simple random sampling. The treatment involved providing formative assessment based on isomorphic problems with feedback. McNemar's test analysis revealed that 13 indicators had p-value <0.05, which means that Ha is accepted, indicating a significant difference in student misconceptions before and after the treatment. Indicator number 10 had p-value of 0.250 (p≥ 0.05), which means that H0 is accepted, signifying no significant difference in student misconceptions before and after the treatment. DQM analysis showed a decrease in misconceptions with an average effectiveness of 92% (high category). The Wilcoxon test resulted in a p-value of 0.000(p< 0.05), thus Ha is accepted, indicating a significant difference in student conceptions before and after the treatment. The conclusion of this study is that there is a significant difference in student misconceptions before and after the treatment using formative assessment with isomorphic problems and feedback with high effectiveness in reducing misconceptions.